ME-Work: Development and Validation of a Modular Meaning in Work Inventory - Schnell, Tatjana; Hoffmann, Carmen (Frontiers in Psychology, 2020)
As research on meaning in work progresses, access to theoretically integrated, differentiated survey instruments becomes crucial (Bailey et al., 2019). In response to this demand, the present article introduces ME-Work, a multidimensional inventory to measure meaning in work. Derived from research findings on meaning in life, the ME-Work inventory offers three modules that can be used separately or jointly. Module 1 assesses four facets of meaning in work, i.e. coherence, significance, purpose and belonging; module 2 measures the subjective assessment of work as meaningful or meaningless, and module 3 records the extent to which work is perceived as a source of meaning. We report on the development of the instrument and the results of an exploratory factor analysis in a pilot study of 115 working adults. A further study with 278 working adults provided evidence for construct and incremental validity. Relationships with meaning in life (SoMe), mental health (PHQ-4), job satisfaction, socio-moral climate (SMC), burnout (MBI-GS) and work as meaning (WAMI) were investigated. Confirmatory factor analysis supported the factor structure. Gender-specific analyses of the four facets of meaning’s differential predictive power provided additional insights. Practical implications and further research needs are discussed.